ChemInform Abstract: Stereoselective Synthesis of Scyphostatin Hydrophilic Moiety. Issue 41 (7th October 2014) - Kuwata, Kazuaki; Suzuki, Masashi; Inami, Yoshikazu; Hanaya, Kengo; Sugai, Takeshi; Shoji, Mitsuru
Abstract The stereoselective synthesis of the title compound (I) is accomplished, which can give access to scyphostatin (II) and its derivatives.